2013
DOI: 10.1590/s1517-83822013000300048
|View full text |Cite
|
Sign up to set email alerts
|

Endo-and exoglucanase activities in bacteria from mangrove sediment

Abstract: The mangrove ecosystem is an unexplored source for biotechnological applications. In this unique environment, endemic bacteria have the ability to thrive in the harsh environmental conditions (salinity and anaerobiosis), and act in the degradation of organic matter, promoting nutrient cycles. Thus, this study aimed to assess the cellulolytic activities of bacterial groups present in the sediment from a mangrove located in Ilha do Cardoso (SP, Brazil). To optimize the isolation of cellulolytic bacteria, enrichm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…Understanding the nitrogen-fixing bacteria-mangrove model system is essential to study the interaction of molecular mechanisms involved. Soares Junior et al (2013) isolated different taxonomical groups of cellulolytic bacteria from mangrove sediments (Alphaproteobacteria, Gammaproteobacteria, Actinobacteria, Firmicutes and Bacteroidetes) and reported that mangrove soils harbor cellulolytic organisms with distinctive characteristics that can be further explored for cellulose degradation for distinct purposes.…”
Section: Maintain Biodiversitymentioning
confidence: 99%
“…Understanding the nitrogen-fixing bacteria-mangrove model system is essential to study the interaction of molecular mechanisms involved. Soares Junior et al (2013) isolated different taxonomical groups of cellulolytic bacteria from mangrove sediments (Alphaproteobacteria, Gammaproteobacteria, Actinobacteria, Firmicutes and Bacteroidetes) and reported that mangrove soils harbor cellulolytic organisms with distinctive characteristics that can be further explored for cellulose degradation for distinct purposes.…”
Section: Maintain Biodiversitymentioning
confidence: 99%
“…A previous study reported the isolation and identification of important enzymes, such as amylase, esterase, cellulose, and protease from endophytes of mangroves (Castro et al, 2014). Further, production of exo-and endoglucanases have been reported in different groups of bacteria isolated from mangrove sediments (Soares Júnior et al, 2013). In a recent study, cellulaseproducing bacterial strains of genus Bacillus and Brucella were isolated from mangrove soil (Behera et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of lignocellulosic biomass such as rice straw is done by the collaboration of many microorganisms, including diverse fungal and bacterial genera producing a variety of cellulolytic enzymes under aerobic or anaerobic conditions. Cellulolytic microorganisms can degrade cellulose-based plant litter (Soares et al 2013). Cellulose is a linear polymer of glucose linked through ß-1,4-glycosidic linkages that is the primary structural material of the plant cell wall and is the most abundant carbohydrate in nature (Saha et al 2006).…”
Section: Introductionmentioning
confidence: 99%